AKTUALISASI NILAI KARAKTER MAJA LABO DAHU UNTUK PENCEGAHAN KASUS BULLIYING PADA ANAK USIA DINI DI TK SATU ATAP SAKURU - Hajrah; Ihlas; Kusumawati, Yayuk (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The phenomenon of increasing cases of bullying among early childhood has become a serious concern in the world of education, including in the environment of Sakuru One Roof Kindergarten. This condition requires a prevention strategy that is not only disciplinary in nature, but also rooted in local cultural values. The value of Maja Labo Dahu, which means being ashamed of doing wrong and afraid of violating social norms, is used as the basis for character building so that children are able to respect themselves and others. This study aims to describe the process of actualizing the character value of Maja Labo Dahu and its implications for the prevention of bullying cases among early childhood at Sakuru One Roof Kindergarten. The type of research used is descriptive qualitative research with a case study approach. Data sources were obtained from the principal, teachers, parents, and students. Data collection techniques were carried out through observation, in-depth interviews, and documentation of learning activities and children's social interactions at school. The collected data was then analyzed using data reduction, data presentation, and conclusion drawing techniques according to the Miles and Huberman model. The results of the study showed that the process of actualizing Maja Labo Dahu values had been systematically implemented through activities such as morning circles, character-based thematic learning, mutual respect, teacher role modeling, extracurricular activities, and collaboration with parents. The implications of applying these values are evident in the formation of mutual respect, increased social empathy, emotional control, and the creation of a friendly and anti-violence school environment. Thus, the Maja Labo Dahu values have proven to be effective in preventing bullying behavior while strengthening children's moral character from an early age.